Faktor-faktor yang Memengaruhi Penawaran dan Permintaan Kopi Indonesia di Pasar Dunia - Adevia, Juli; Napitupulu, Tia Sofiani; Al'Fatah, A'ung Ezra (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
This study aims to analyze the factors influencing the supply and demand of Indonesian coffee in the world market. The analysis reveals that the supply of Indonesian coffee is affected by the cultivated area and the minimum wage of labor. Meanwhile, the demand for Indonesian coffee is influenced by sugar prices and increases in per capita income. The price of Indonesian coffee is determined by supply, demand, and the world coffee price. Coffee exports from Indonesia, Brazil, Vietnam, and Colombia are influenced by each country's exchange rate against the US Dollar and global coffee demand. The supply of Brazilian coffee is affected by coffee prices and minimum wages, while its demand is influenced by sugar prices and per capita income. The prices of Brazilian and Vietnamese coffee are influenced by world coffee prices. The supply of Vietnamese and Colombian coffee is determined by the size of the cultivated area. The demand for Vietnamese coffee is influenced by coffee prices, sugar prices, and per capita income. Meanwhile, the demand for Colombian coffee is primarily affected by per capita income, and its price is influenced by coffee supply and world coffee prices. Coffee imports by the United States, Germany, Italy, Japan, and the United Kingdom are influenced by per capita income, world coffee prices, and the previous year’s coffee prices. The world price of coffee is affected by the ratio of exports to world coffee supply.